Refocusing the climate services lens: Introducing a framework for co-designing “transdisciplinary knowledge integration processes” to build climate resilience - Elizabeth Daniels; Sukaina Bharwani; Åsa Gerger Swartling; Gregor Vulturius; Karen Brandon (Climate Services, 2020)
This paper seeks to reconceptualize climate services in light of the prevailing inability of existing climate information to spur needed policy and action. We propose refocusing the climate services lens by moving away from a narrow, supply-driven emphasis on products. Instead, we advocate moving towards a process-centric approach defined by transdisciplinary collaboration that purposefully seeks to bring about fundamental, long-term benefits. Such benefits include increased human and institutional capacity, and the creation of relationships that are essential components of science-informed decision-making for climate adaptation and beyond. Work underpinning this paper consists of a review of existing climate services guidance, and analyses of a survey of climate services stakeholders, and a climate information co-production process case study in Lusaka, Zambia. We identify elements needed to support complex, real-world decision-making that many existing climate services fail to sufficiently consider. We respond by introducing a framework (Tandem), which consists of structured elements and practical, guiding questions informed by empirical analysis. To lay the foundation for both science-informed policy and policy-informed science, the Tandem framework puts forward guidance to achieve three goals: 1) to improve the ways in which all participants work together to purposefully design transdisciplinary knowledge integration processes (co-exploration and co-production processes that bring together different knowledge types across the science-society interface); 2) to co-explore decision-relevant needs for the co-production of integrated climate information (i.e., decision-relevant climate and non-climate information); and, 3) to increase individual and institutional capacities, collaboration, communication and networks that can translate this information into climate-resilient decision-making and action.